Civil servants' perspectives on the role of citizens in public service delivery in Uganda - Wenene, Mary Theopista; Rutgers, Mark R.; Steen, Trui (2016)
In this article we study civil servants perceptions about the role of citizens in the provision of public services in Uganda. In other words, we examine the views of those who deliver civil services regarding the actual and desired influence of service recipients. An empirical study was conducted focusing on the health and education sectors in Uganda. It is concluded that due to a number of tensions regarding the role of the citizen in Uganda, civil servants feel that service recipients are not yet adequately engaged in the demand for and delivery of quality public services. More effective public service delivery in Uganda cannot be achieved without the development of a culture that supports the building of capacity at all levels, including the community and individual service recipients. - Reproduced.
Keywords: Public administration - Uganda; Civil service - Uganda; Civil service